Territorialidades e proteção social: conflitos socioambientais indígenas vivenciados na pesca artesanal no litoral norte da Paraíba - Silva, Emanuel Luiz Pereira da (2016)
This thesis deals with the territorial expressions of the social question of indigenous people called the Potiguaras belonging to the Environmental Protection Area of the Mamanguape city on the north coast of Paraiba. It aims, from territoriality, analyze the dynamics of the relationships that shape the social and environmental protection arising from artisanal fisheries in the village Tramataia. It starts from the following assumption: the existence of overlapping territorial scales imposed on Potiguaras indigenous people expressed in the productive dynamics of artisanal fisheries, either by economic agents, whether by public officials who interact and conflict in contention for and experiences of territory. The route mapped out for this study, led us to an ethnoecologic and ethnobiological approach that sought transversely in other areas of knowledge, analysis of existing territorial overlaps; of territorial-dispossession, repossession processes of indigenous lands; elucidation of collective experiences within the research as uptake of mediation and analysis of the contradictions inherent in social processes of labor incorporation in artisanal fisheries by commercial logic of carcinoculture. This process made it possible to elucidate thatcthe artisanal fisheries will continue to be an attractive economic activity, both for survival status of indigenous peoples as the maintenance of this protected territory. However, the developed experiments point to the need to strengthen this territory belonging to indigenous people (since its inception), to a renewed environmental management or "modernized" where supervision is exercised as similar environmental audit practice. It allows us to say that the livings of artisanal fisheries in the APA of Mamanguape city suffer conflicting interference due to existing connections with the productive dynamics of contemporary capitalism, expressed in that territory by carcinoculture. However, the first Conference of Indigenous Policy in Paraiba has great potential to set up as a driving force for social transformation. In this space, in this begining of century, it affirms as openness to the dialogue and persuasion between civil society and public officials. It is expected that a new participatory cycle can expand its corporate face and at the same time promote a more immediate connection between the consultation of indigenous society and the effectiveness of the decisions in the implementation of public policies